2009
DOI: 10.1038/aps.2009.18
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated expression of UHRF1 reduces the radiosensitivity of cervical cancer HeLa cells to γ-irradiation

Abstract: Aim: An in vitro study was carried out to determine the effect of UHRF1 overexpression on radiosensitivity in human cervical cancer HeLa cells using adenovirus-mediated UHRF1 gene transfer (Ad5-UHRF1). Methods: Cell survival was evaluated using the clonogenic survival assay and the MTT assay; apoptosis and cell cycle distribution were monitored by flow cytometry. Protein levels were measured by Western blotting. Silencing XRCC4 expression was performed by transfection of small interfering RNA (siRNA). Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Similarly, knockdown of UHRF1 in HEK293 and WI-38 cells also renders these cells hypersensitive to X rays, UV light, and hydroxyurea (14). More recently, UHRF1 has also been shown to facilitate the DNA damage response (DDR) to gamma irradiation (15,16). Consistently, DNA damage results in a decrease in the UHRF1 mRNA as well as protein level (1).…”
mentioning
confidence: 62%
“…Similarly, knockdown of UHRF1 in HEK293 and WI-38 cells also renders these cells hypersensitive to X rays, UV light, and hydroxyurea (14). More recently, UHRF1 has also been shown to facilitate the DNA damage response (DDR) to gamma irradiation (15,16). Consistently, DNA damage results in a decrease in the UHRF1 mRNA as well as protein level (1).…”
mentioning
confidence: 62%
“…Furthermore, significant overexpression of UHRF1 has been observed in several types of human tumor, including breast (13,14), bladder (15), prostate (16) and lung cancer (17). The overexpression of UHRF1 has also been reported to reduce the radiosensitivity of human breast cancer cells and HeLa cells to γ-irradiation (18). Previous studies have demonstrated that UHRF1 is an oncogene in hepatocellular carcinoma (19,20 Furthermore, the overexpression of UHRF1 destabilizes and delocalizes DNA (cytosine-5-)-methyltransferase 1 (DNMT1) and causes DNA hypomethylation in cancer cells (19).…”
Section: Introductionmentioning
confidence: 99%
“…UHRF1 is an abnormal expression gene, we screened the radiosensitizing drug using gene-chip, in our previous studies on the gene demonstrated that UHRF1 showed significant radioresistance (13,14), and to further explore its biological functions, we performed a series of experiments in breast cancer MDA-MB-231 cells to explore the effect of UHRF1 on proliferation of cells in vitro, growth of nude mice in vivo and the underlying mechanisms, the role of UHRF1 in regulating invasion and migration was also explored.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact biological functions of UHRF1 are uncertain, previous studies in vitro showed that UHRF1 may be a growth-regulating gene because its expression is regulated during the cell cycle, and it forced post-mitotic cells to proliferate (9,10). The expressions of UHRF1 mRNA and protein were low in quiescent cells and high in proliferating cells and tissues, including breast carcinomas (11), and our previous study also indicated that UHRF1 promoted growth of breast duct cancer BT-549 cells (12), and conferred radioresistance of HeLa cells (13) and breast cancer cells (14), all our results suggested its oncogene traits. However, few studies have explored whether UHRF1 could regulate proliferation in vivo, and affect invasion and migration of breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation